Methane emission, nitrogen excretion, and energy partitioning in Hanwoo steers fed a typical TMR diet supplemented with Pharbitis nil seeds - Bharanidharan, Rajaraman; Xaysana, Panyavong; Hong, Woo Hyeong; Kim, Taehoon; Byun, Jun Suk; Lee, Yookyung; Tomple, Byamungu Mayange; Kim, Kyoung Hoon; Ibidhi, Ridha (Frontiers in Veterinary Science, 2024)
Two in vivo experiments were conducted to evaluate the potential of Pharbitis nil seeds (PA) as an anti-methanogenic additive to ruminant feed. In experiment 1, six Hanwoo steers (459.0 ± 25.8 kg) were fed either a total mixed ration (TMR; 32-d period) or TMR supplemented with PA at 5% dry matter (DM) intake (TMR-PA; 45-d period) for two consecutive periods. Fecal and urine outputs were measured in an apparent digestibility trial in both periods. Methane (CH4) yield and heat energy (HE) were measured using respiratory chambers equipped with gas analyzers. In experiment 2, five rumen cannulated Holstein steers (744 ± 35 kg) were fed the same TMR or TMR-PA diets for 40 days; rumen samples were collected at 0, 1.5, and 3 h after feeding on the last day of the feeding period. In experiment 1, although there were no differences (p > 0.05) in nutrients or gross energy intake (GEI) between the groups, an increase (p < 0.05) in the apparent digestibility of DM (9.1%) and neutral detergent fiber (22.9%) was observed in the TMR-PA fed Hanwoo steers. Pronounced decreases (p < 0.05) in CH4 (g/Kg DM; 17.1%) and urinary N excretion (% N intake; 7.6%) were observed in the TMR-PA group, leading to a 14.7% increase in metabolizable energy intake (% GEI). However, only a numerical increase (p > 0.05) in retained energy was observed due to the increase in HE loss. In experiment 2, a drastic decrease (p < 0.05) in rumen ammonia concentration (56.3%) associated with an increased (p = 0.091) rumen short-chain fatty acid concentration 1.5 h after feeding were observed in TMR-PA fed Holstein steers. A 26.6% increase (p < 0.05) in the propionate proportion during the treatment period clearly reflected a shift in the ruminal H2 sink after 3 h of feeding. A 40% reduction (p = 0.067) in the relative abundance of rumen protozoa Entodinium caudatum was also observed. It was concluded that PA could be a natural feed additive for CH4 and N emission abatement.